Pre-existing medical disorders as risk factors for preeclampsia: an exploratory case-control study - Linglan Pan; Zhen Fu; Ping Yin; Dunjin Chen (Taylor & Francis Group, 2019)
Objective: We sought to explore pre-existing medical disorders as risk factors for preeclampsia as thoroughly as possible. Methods: A case-control design. A group of 1,652 patients were identified as the preeclampsia group, and another randomly selected 4,500 patients were identified as the non-preeclampsia group. Results: Mature ovarian teratoma (adjusted odds ratio [OR] 7.69, 95% CI 1.58-37.53), uterine fibroids (adjusted OR 2.24, 95% CI 1.28-3.92) and pregestational hypothyroidism (adjusted OR 5.17, 95% CI 2.43-11.00), were significantly correlated with preeclampsia. Conclusions: Mature ovarian teratoma, uterine fibroids and pregestational hypothyroidism may also contribute to the incidence of preeclampsia.